Assessment of Cocoon and Egg Productivity in Selected Strains of Eri Silkworm through Consumption and Utilization Indices - Prakash, B.K.; Sannappa, B. (International Journal of Scientific Research in Biological Sciences, 2018)
Silkworm nutrition deals with the substances required for growth and production of proteinaceous silk fiber. The quantum of food consumption, utilization and conversion efficiency into body mater for production of silk mainly governed by the type of host/variety on which silkworm feeds and also strain/breed of silkworm. In the current investigation, selected eri silkworm (Samia cynthia ricini Boisduval) strains (Blue-Plain, Blue-Zebra, Blue Greenish-Plain, White-Plain, White-Zebra, Yellow-Plain, Yellow-Spotted and Yellow-Zebra) were reared using Local Pink castor leaf to assess the efficiency of ingestion, digestion and conversion of food for production of unit quantity of cocoon, shell and eggs. The study revealed that, among the eri silkworm strains White-Plain larvae exhibit significantly least ingesta and digesta to produce a gram of cocoon and shell and it was more with White-Zebra both on fresh and dry weight basis, respectively. The efficiency of conversion of ingested food and digested food into cocoon and shell both on fresh and dry weight basis was significantly better with White-Plain, least values were found with Blue-Plain and Yellow-Spotted for ingested food and digested food, respectively. In respect of leaf-egg ratio, White-Plain strain stood best over other strains with least being in Yellow-Zebra strain. The study inferred that, White-Plain strain of eri silkworm performed better by recording higher efficiency in consumption and utilization of food for eri cocoon and egg production.